Gerakan Masyarakat Bijak Konsumsi Obat (GMBKO) pada Masyarakat Desa Liang Ulu Kecamatan Kota Bangun Kabupaten Kutai Kartanegara - Ahmad, Islamudin; Arifuddin, M.; Samsul, Erwin; Maulidha, Faizatun; Mus, Nurul Muhlisa (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Medicine is an inseparable part of society because of its usefulness in reducing symptoms or curing a disease. In order for medicines to provide maximum results, a correct understanding of the rules for consuming medicines, whether in the form of synthetic drugs or those of natural origin from plants, is required. One area that is rich in medicinal plants, including endemic Kalimantan medicinal plants such as kratom and has attention to the use of medicinal plants to improve health status, is Liang Ulu Village. To provide understanding and increase the knowledge of the people of Liang Ulu Village, Kota Bangun District, Kutai Kartanegara Regency regarding the proper and correct use of medicines and medicinal plants, community service activities were carried out in the form of the Community Wisely Consuming Medicines (MBKO) movement. The service methods used include delivering material, discussions, and distributing posters and leaflets. Success parameters are seen based on pre and post-test data to measure the increase in public understanding. The results of community service activities show an increase in knowledge from 62.56% to 82%.